MODELING OF HYDRODYNAMIC AND HEAT AND MASS TRANSFER PROCESSES IN ABSORPTION OF THE DRYING AIR EMISSIONS - Gennadevna, Shchedrina Galina (Journal of Applied Engineering Science, 2019)
High efficiency drying wet gases are film contact apparatus chlorotoluene installations. The object of the study is ventilation emissions characterized by high moisture content. The paper presents a mathematical model of the absorption drying of wet ventilation emissions for devices with a regular nozzle of rigidly fixed porous plates of microporous plastic. The obtained criterion equations allow to carry out engineering calculations of air drying absorption devices.